Bilateral visual loss after selective artery embolization in the neck for hemorrhage of malignant tumor. (March 2023) - Liang, Zhong-Shuai; Wei, Li-Chun; Luo, Chang-Zhi; Wang, You-Fu
Abstract: Introduction and importance: Currently, selective arterial embolization (SAE) has been widely applied for the treatment of many diseases due to its minimal invasiveness. But the complications caused by SAE can be serious. Case presentation: Here, we report a case of a patient who experienced bilateral blindness 4 h after selective arterial embolization (SAE). A 67-year-old man, with a 13-year history of nasopharyngeal carcinoma, was admitted to our hospital for nasopharyngeal carcinoma hemorrhage and was scheduled for SAE. The patient did not have any thromboembolic complications. His had a platelet count of 43 × 109/L (range 150–400 × 109/L) and a prothrombin time (PT) of 9.3 s. The surgery was completed under local anesthesia. However, 4 h after the surgery, the patient complained of visual loss. We performed a fundoscopy examination, which showed bilateral ophthalmic artery embolism. Clinical discussion: Bilateral ophthalmic artery embolism is fatal to vision. When this occurs, it would be difficult to save the eyes. So, the relevant selection of the optimal properties of the used PVA and coil embolization materials is important during SAE. Conclusion: It is important to improve the existing understanding of the involvement various vessels during embolization of head and neck tumors. Furthermore, special and paramount attention is to be paid to the specific pre-operative angio-architecture, particular patient condition, and the prudent choice of embolic material to prevent the occurrence of ectopic embolization. Highlights: Bilateral blindness 4 h after selective arterial embolization is rare. We suggest some recommendations to avoid the complication of blindness. We give some suggestion about the selective arterial embolization.